Roles of oral anticoagulant use on the risk of 28-day mortality and in-hospital mortality in patients with acute respiratory distress syndrome - Huang, Jiayang; An, Huijie; Cheng, Lin; Li, Wangsheng; Zhang, Ke; Su, Dan (Frontiers in Pharmacology, 2025)
AimThis study was to investigate the association between oral anticoagulant use and 28-day mortality and in-hospital mortality in patients with acute respiratory distress syndrome (ARDS).MethodsA total of 1754 ARDS patients were identified in database from 2008 to 2022 in this cohort study. Univariable and multivariable cox regression models were applied to assess the associations of oral anticoagulant use with the risk of 28-day mortality and in-hospital mortality. Propensity score matching (PSM) was performed in ARDS patients according to whether they were taking oral anticoagulants or not to control potential bias. Subgroup analysis was performed according to severity of ARDS (mild, moderate, and severe), and comorbidities (atrial fibrillation, sepsis, and AKI). Hazards ratio (HR) and respective confidence interval (CI) were presented.ResultsIn total, 7758 patients not receiving oral anticoagulant and 905 patients receiving oral anticoagulant. The reduced risk of 28-day mortality in ARDS patients was identified in those undergoing oral anticoagulant use (HR = 0.32, 95%CI: 0.24–0.44). Oral anticoagulant use was associated with reduced risk of in-hospital mortality (HR = 0.27, 95%CI: 0.20–0.37). After adjusting for the respective confounding factors, the associations of Warfarin with decreased risk of 28-day and in-hospital mortality were not significant (P > 0.05).ConclusionOral anticoagulant was related to decreased risk of 28-day/in-hospital mortality in patients with ARDS. Warfarin and novel oral anticoagulants showed no significant difference on 28-day/in-hospital mortality in patients with ARDS.